Environmental performance and economic feasibility in an interlocking concrete paving industry - Souza, Adriana Ireno de; Casimiro, Leonardo Alves de Oliveira; Sandri, Emanuel Campigotto; Johann, Jerry Adriani; Bertolini, Geysler Rogis Flor (Revista de Administração da UFSM, 2020)
Purpose – This study’s main objective is to verify if there is a relation between proactivity and technological protection in the environmental performance of the ventures in this segment. And check if there is economic feasibility to produce interlocking concrete paving blocks with the addition of rubber, as well as the certification of the product as ecologically friendly. Design/methodology/approach – The study is based on the methodologies shown by Dickel (2017), questionnaire and variables, and Bertolini (2009), economic viability for the manufacture of ecologically friendly products. Findings – As a result, the study confirms the association between technological protection and proactivity in environmental performance, as well as the economic viability for the offer of the interlocking concrete paving product with ecological certification. Originality/value – Civil construction occupies a prominent position, accounting for a significant portion of Brazil's Gross Domestic Product (GDP), as well as being the largest employer industry in the country. It is also recognized as having significant environmental impacts in the conduct of its activities. However, the search for sustainability has been a mobilizing element in the definition of corporate strategies, companies have been seeking more and more actions that are economically viable, respecting environmental and social aspects.